2010
DOI: 10.1167/iovs.09-4538
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Histone Deacetylase Protects the Retina from Ischemic Injury

Abstract: PURPOSE. The pathogenesis of retinal ischemia results from a series of events involving changes in gene expression and inflammatory cytokines. Protein acetylation is an essential mechanism in regulating transcriptional and inflammatory events. The purpose of this study was to investigate the neuroprotective action of the histone deacetylase (HDAC) inhibitor trichostatin A (TSA) in a retinal ischemic model. METHODS. To investigate whether HDAC inhibition can reduce ischemic injury, rats were treated with TSA (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 41 publications
3
70
1
Order By: Relevance
“…On the other hand, HDACs could affect MMP-2 and MMP-9 expression indirectly, possibly by regulating the levels of inflammatory cytokines expressed and released in the infarct and border zones. We have shown that TSA treatment represses the induction of retinal TNF-␣ levels in rats subjected to retinal ischemia (13). Another study (24) has shown that long-term treatment with SAHA reduced circulating levels of multiple inflammatory cytokines, including TNF-␣, IL-1␤, and IL-6, in the rat DOCA-salt model of hypertensive cardiomyopathy.…”
Section: Discussionmentioning
confidence: 71%
“…On the other hand, HDACs could affect MMP-2 and MMP-9 expression indirectly, possibly by regulating the levels of inflammatory cytokines expressed and released in the infarct and border zones. We have shown that TSA treatment represses the induction of retinal TNF-␣ levels in rats subjected to retinal ischemia (13). Another study (24) has shown that long-term treatment with SAHA reduced circulating levels of multiple inflammatory cytokines, including TNF-␣, IL-1␤, and IL-6, in the rat DOCA-salt model of hypertensive cardiomyopathy.…”
Section: Discussionmentioning
confidence: 71%
“…This review includes a short overview of genetic associations between HDACs and the etiology of diabetes followed by a discussion of the potential for HDACi as an oral therapy with respect to modulation of the immune system, insulin resistance, β-cell development, differentiation and function, and pathogenetic events relevant for β-cell failure and destruction and islet graft rejection. Of note, HDACi also hold promise with respect to treatment of late diabetic complications such as diabetic nephropathy (28,29) and retinal ischemia playing a central role in diabetic retinopathy (30). HDACi and late diabetic complications will not be discussed further here, and readers are referred to the aforementioned references.…”
Section: Antiinflammatory Properties Of Histone Deacetylase Inhibitorsmentioning
confidence: 99%
“…23 Briefly, we photographed 3 standard rectangular areas (0.2 · 0.2 mm; 0.04 mm 2 ) at 1, 2, and 3 mm, respectively, from the optic disc in the central region of each retinal quadrant (superotemporal, inferotemporal, superonasal, and inferonasal). Thus, for each retina, 12 rectangles were evaluated, for a total area of 0.48 mm 2 (12 · 0.04 mm 2 ), which is *1% of the total area of the retina, 24 assuming an average area of 50 mm. 2 To determine the density of FG-positive RGCs as cells/mm, 2 we multiplied the number of cells per 0.04 mm 2 by 25.…”
Section: Retrograde Labeling Of Rgcsmentioning
confidence: 99%